The Meisenheimer complex as a paradigm in drug discovery: reversible covalent inhibition through C67 of the ATP binding site of PLK1 - Pearson, Russell J.; Blake, David G.; Mezna, Mokdad; Fischer, Peter M.; Westwood, Nicholas J.; McInnes, Campbell (Elsevier, 2018)
The polo kinase family are important oncology targets that act in regulating entry into and progression through mitosis. Structure-guided discovery of a new class of inhibitors of Polo-like kinase 1 (PLK1) catalytic activity that interact with Cys67 of the ATP binding site is described. Compounds containing the benzothiazole N-oxide scaffold not only bind covalently to this residue, but are reversible inhibitors through the formation of Meisenheimer complexes. This mechanism of kinase inhibition results in compounds that can target PLK1 with high selectivity, while avoiding issues with irreversible covalent binding and interaction with other thiol-containing molecules in the cell. Due to renewed interest in covalent drugs and the plethora of potential drug targets, these represent prototypes for the design of kinase inhibitory compounds that achieve high specificity through covalent interaction and yet still bind reversibly to the ATP cleft, a strategy that could be applied to avoid issues with conventional covalent binders.